Cost optimization of drilling operations in open-pit mines through parameter tuning. Issue 2 (3rd March 2020) - Ugurlu, Omer Faruk; Kumral, Mustafa
ABSTRACT: Problem statement : Increasing efficiency and performance of bench drilling in open-pit mines has the potential to generate considerable savings. This increase can be realized by monitoring the drilling operation, analyzing monitoring data with statistical tools and optimizing operational variables. Finding the best configuration of controllable drilling parameters (e.g. rotation speed, pulldown force and bailing air pressure) and determining replacement time of drill bits would assist to increase penetration rate and optimize drilling operation cost. Approach : In this paper, the effects of controllable variables on drilling performance are quantified by the face-centered central composite design, and the replacement time of drill bits is optimized using the genetic algorithm. Results : Results show that the proposed approach could be used to determine the optimal drilling parameters and minimize the energy cost in open-pit mines. Abbreviations: FCCCD: face-centered central composite design; RPM: revolutions per minute; PDF: push down force; BAP: bailing air pressure; ANOVA: analysis of variance